Dinâmica da produção imobiliária em Sorocaba - Cruz, Talita Anunciação (Universidade Federal de São Carlos, 2024)
The primary objective of the research is to analyze real estate development in Sorocaba, focusing on the vertical residential segment and how it influences the city's urban space organization. The study covers the period from 2010 to 2023, extending to August 2024, and centers on the actions of key real estate market players, such as developers and construction companies. The investigation uses the theory of urban space production, emphasizing that space not only reflects social needs but is a product of capitalist production relations. In this context, urban land becomes a valued commodity, and housing becomes a financial asset, which shapes the city in an unequal way. The study demonstrates that the verticalization of the most valued areas, or those undergoing a valuation process, contributes to socio-spatial segregation, as higher-income classes occupy these areas while low-income populations are pushed to peripheral regions. Additionally, it is observed that urban infrastructure, such as transportation and public services, is directed toward areas undergoing valuation, reinforcing inequality in the distribution of resources. The results indicate that the real estate market in Sorocaba, specifically in the vertical segment, has been a significant driver of urban transformation, with profound impacts on the production and reproduction of urban space. In conclusion, the research reveals that real estate development in Sorocaba follows a capitalist logic of accumulation, organizing urban space in an unequal and exclusionary manner, with significant consequences for the city's socio-spatial structure.
Real estate production dynamics in Sorocaba
Keywords: Produção do Espaço Urbano; Mercado Imobiliário; Apartamentos; Sorocaba; Urban Space Production; Real Estate; Apartaments; CIENCIAS HUMANAS::GEOGRAFIA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA